Hip fractures: mortality and correlation with preoperative comorbidities in Indian elderly population - Padhi, Prashant Pratim; Rai, Pankaj (International Journal of Research in Orthopaedics, 2021)
Background: Hip fractures are an emerging health care problem due to increase in the elderly population all over the world and the associated complications, morbidity and mortality. The objective of this study is to find out the mortality rates in Indian elderly population with hip fractures and to establish an association between various related complications pre and post operatively for a better risk stratification. Methods: A prospective observational cohort study, was carried out at a high-volume orthopaedic centre from 2009 to 2018. And all patients managed for hip fractures were followed up till death or 05 years. Results: The age adjusted first-year mortality was found to be 33% with statistically significant increase in the mortality in individuals with three or more pre-op comorbidities. The significantly associated co-morbidities were chronic renal failure (Hazard ratio 2.32 with CI 1.65- 3.24) and diabetes mellitus (Hazard ratio 1.66 with CI 1.25 – 2.21). There has been a significant dip in the cumulative survival rates of these individuals irrespective of age, sex, preop anaemia. Conclusions: A knowledge about the comorbidities/ risk factors and the extent to which they influence the long-term survival in the geriatric hip fracture patients can help treating physician to effectively prioritise and plan management in coordination with allied specialities.